La censure de l’imprimé au Portugal sous Salazar : omniprésente, presque omnipotente - Daniel Melo; Luís Augusto Costa Dias † (Amnis)
This article analyses the origins and functioning of censorship in Portugal under the dictatorships of Salazar (1933-1968) and Marcelo Caetano (1968-1974).